Reduction of Oral Mucositis Severity using a Topical Vasoconstrictor in Bone Marrow Transplant Patients - Li, Ningfeng Fiona; Fahl, William E. (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Grade 3 oral mucositis (OM) is historically observed in >90% of bone marrow transplant patients who received the cyclophosphamide + total body irradiation (CY+TBI) conditioning regimen. It was previously shown that orotopically applied adrenergic vasoconstrictor prevented up to 100% of radiation-induced oral mucositis in two preclinical animal models. Adrenergic vasoconstrictor (i.e., phenylephrine in an aqueous-alcohol NG11-1 formulation) was orotopically applied to three patients (ages 24-29) who received the CY+TBI conditioning regimen; they were compared to five matched controls who received no orotopical vasoconstrictor. All patients received the CY+TBI conditioning regimen for acute lymphoblastic leukemia within the University of Wisconsin Adult Bone Marrow Transplant Program. Over the seven-day CY+TBI conditioning regimen, 20 min before each treatment, either radiation or chemotherapy, vasoconstrictor was applied topically to the oral cavity, and patients then received either 1.5 Gy whole-body radiation or IV cyclophosphamide. OM severity was scored over a three-week period using: i) physical assessments, ii) daily photos of the oral cavity, iii) oral pain and oral function score sheets, and iv) recorded narcotic consumption. Both “Grade 3 OM” duration and “any OM” duration in vasoconstrictor-treated patients were substantially lower than for the five control patients. Though nasogastric tube or total parenteral nutrition were used in 3 out of 5 control patients, there was no use of these supportive care measures in the three vasoconstrictor-treated patients. Orotopically applied NG11-1 vasoconstrictor formulation substantially reduced the incidence and severity of “Grade 3” and “any” oral mucositis when compared to matched control patients, all of whom received the same CY+TBI conditioning regimen. The liquid orotopical formulation was easily tolerated by patients both in its ease of use and lack of side effects.